1941
DOI: 10.4102/abc.v4i1.1720
|View full text |Cite
|
Sign up to set email alerts
|

The South African Species of Erythrina.

Abstract: No abstract available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1947
1947
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Origin of the polyploid species.-There is no evidence that the polyploid species, E. acanthocarpa and E. amaeonica, 2n = 84,. are of common origin or close relationship. E. acanthocarpa is South African and according to Collett (1941) "is limited to the Queenstown-Tarkastad-Cathcart area of the eastern Cape Province where these shrubs are said to form dense thickets." E. amazonica has been collected in several widely removed areas in Amazonian Peru and Brazil, but little is known concerning its ecological relationships.…”
Section: E Embryanamentioning
confidence: 99%
See 1 more Smart Citation
“…Origin of the polyploid species.-There is no evidence that the polyploid species, E. acanthocarpa and E. amaeonica, 2n = 84,. are of common origin or close relationship. E. acanthocarpa is South African and according to Collett (1941) "is limited to the Queenstown-Tarkastad-Cathcart area of the eastern Cape Province where these shrubs are said to form dense thickets." E. amazonica has been collected in several widely removed areas in Amazonian Peru and Brazil, but little is known concerning its ecological relationships.…”
Section: E Embryanamentioning
confidence: 99%
“…Krukoff (1939bKrukoff ( , 1941 surveyed the American species, reduced the synonymy, and clarified specific limits. Treatments of the tropical African species have been presented by Baker (1929), Congolian species by Louis (1938) and South A,frican species by Collett (1941). The Asiatic, Polynesian and Australian species, although the subject of preliminary study by Krukoff (1939a), are yet to receive adequate taxonomic attention.…”
mentioning
confidence: 99%
“…and E. zeyheri Harv.) also have folded standard petals (Figure 1D; Collett, 1941; Jacot Guillarmod et al, 1979), which are similar to those of the tubular‐shaped hummingbird‐pollinated species. Based on phylogenetic analyses of plastid DNA and morphological characters, Bruneau (1996, 1997) suggested that hummingbird pollination had evolved several times independently in Erythrina together with the tubular flower morphology.…”
Section: Figurementioning
confidence: 66%